2016
DOI: 10.1016/j.psychres.2016.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Combined therapy with interpersonal psychotherapy adapted for borderline personality disorder: A two-years follow-up

Abstract: Highlights IPT-BPD plus drug was superior to single drug after 32 weeks trial. Difference persisted at 24 months follow-up for impulsivity and relationships. It also persisted for perception of psychological and social functioning. Differences concerning anxiety and affective instability were lost after 6 months. The most of benefits of combining IPT-BPD endured two years after termination. AbstractFew investigations evaluated the long-term effects of psychotherapies in borderline personality disorder (BP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…Results showed that patients treated with the combination of fluoxetine and DBP did not evidence any additional benefits over placebo + DBT treatment on self-report measures of depression, anxiety, anger, dissociation, and global functioning. Different findings were obtained by two controlled studies [30,31] aimed to evaluate the short and long-term efficacy of combined therapy with fluoxetine (20-40 mg/day) and Interpersonal Psychotherapy adapted to BPD (IPT-BPD) in a sample of 55 BPD outpatients. In particular, combined therapy with adapted IPT was found superior to single fluoxetine after 32 weeks of treatment, concerning core symptoms of the disorder (interpersonal relationships, affective instability, and impulsivity), anxiety, and quality of life [30].…”
Section: ) Antidepressantsmentioning
confidence: 99%
See 3 more Smart Citations
“…Results showed that patients treated with the combination of fluoxetine and DBP did not evidence any additional benefits over placebo + DBT treatment on self-report measures of depression, anxiety, anger, dissociation, and global functioning. Different findings were obtained by two controlled studies [30,31] aimed to evaluate the short and long-term efficacy of combined therapy with fluoxetine (20-40 mg/day) and Interpersonal Psychotherapy adapted to BPD (IPT-BPD) in a sample of 55 BPD outpatients. In particular, combined therapy with adapted IPT was found superior to single fluoxetine after 32 weeks of treatment, concerning core symptoms of the disorder (interpersonal relationships, affective instability, and impulsivity), anxiety, and quality of life [30].…”
Section: ) Antidepressantsmentioning
confidence: 99%
“…Whilst fluoxetine received the greatest research attention out of SSRIs tested, [25][26][27][28][29][30][31], only one report of the efficacy of fluvoxamine and one of treatment with sertraline have been published to date [32,33].…”
Section: ) Antidepressantsmentioning
confidence: 99%
See 2 more Smart Citations
“…The second of our studies [42] was aimed to verify whether the benefits from the addition of interpersonal psychotherapy to pharmacotherapy after 32 weeks of treatment persisted during a follow-up period of two years after termination of psychotherapy. Forty-four patients who completed the 32 weeks trial (22 who received combined therapy and 22 who received single fluoxetine) underwent 24 months of follow-up.…”
Section: Controlled Trials Of Ipt-bpd: Efficacy Follow-up and Predicmentioning
confidence: 99%